The Role of Kuttab in Indonesia as an Agent of Religious Values Socialization from a Structural Functional Perspective - Wahyuni, Fauziah Sri; Sucianingsih, Sucianingsih (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study aims to describe the role of Kuttab in Indonesia as an agent for the socialization of religious values in the context of modernization. The research employs a Systematic Literature Review (SLR) methodology, analyzing scientific articles published between 2014 and 2024. Talcott Parsons' Structural Functional Theory is used to examine how Kuttab adapts, functions, and remains relevant within modern Islamic education. The findings reveal that Kuttab successfully adapts to modernization through an independent curriculum rooted in classical Islamic teachings, such as the Qur'an and Hadith, while integrating contemporary knowledge. Technology is utilized selectively to support learning without compromising religious principles. Additionally, Kuttab actively socializes faith and moral values, not only through classroom activities but also by involving parents in the learning process. The success of Kuttab in maintaining its relevance depends on the integration of internal components (educators, students) and external factors (parents, community, government). Traditional educational methods, such as lectures and memorization, are preserved to maintain Islamic cultural heritage and shape young generations with strong Islamic character. This study offers practical insights for modern Islamic educational institutions to design adaptive curricula that remain rooted in traditional values and emphasizes parental involvement in education. The findings also support Structural Functional Theory, highlighting the importance of integration in maintaining social stability through education.